Replication of Influenza D Viruses of Bovine and Swine Origin in Ovine Respiratory Explants and Their Attachment to the Respiratory Tract of Bovine, Sheep, Goat, Horse, and Swine - Mazzetto, Eva; Bortolami, Alessio; Fusaro, Alice; Mazzacan, Elisa; Maniero, Silvia; Vascellari, Marta; Beato, Maria Serena; Schiavon, Eliana; Chiapponi, Chiara; Terregino, Calogero; Monne, Isabella; Bonfante, Francesco (Frontiers in Microbiology, 2020)
Bovine is considered the main reservoir of influenza D virus (IDV), however, low levels of seropositivity in other farmed species suggest a wide range of potential hosts. Nevertheless, it is not clear whether this scenario is the result of rare spillover events upon contact with bovines, or a lack of adaptation of IDV to these hosts. Among these species, sheep represents a crucial component of the rural economy in many developing countries, but little is known about its role in the ecology of the disease. To evaluate the susceptibility of sheep to IDV viruses of different origin, we used ovine respiratory tissues as an ex vivo model and investigated the infective phenotype of two IDV strains isolated from either bovine (IDV-BOV) or swine (IDV-SW). For translatability purposes, we included a parainfluenza type 3 virus, as positive control, given its known respiratory tropism in sheep. We performed a timed evaluation of the viral infectivity, cell tropism and the associated histopathology, by means of tissue culture infectious dose assays on supernatants and histological/immunohistochemical analyses on explanted tissues, respectively. To further investigate differences in the phenotype of these two strains and to identify the potential targets of replication in the most commonly land-based farmed mammalian species, we carried out virus binding assays on histological sections of the respiratory tract of bovine, caprine, ovine, horse and swine. Our results demonstrated that IDV successfully replicates in nasal, tracheal and lung ovine tissues, suggesting a moderate susceptibility of this species to IDV infection. Interestingly, despite the high genetic identity of these strains, IDV- BOV consistently replicated to higher titers than IDV-SW in all respiratory tracts, suggesting IDV viruses might display considerable levels of variability in their phenotype when crossing the species barrier. Virus binding assays confirmed a superior affinity of the IDV viruses for the bovine upper respiratory tract, and a preference for the pharyngeal epithelium of small ruminants, indicating possible targets to improve the sensitivity of virological sampling for diagnostic and post-mortem purposes. Further pathogenesis and cross-species transmission studies will be necessary to elucidate the ecology of IDV and eventually allow the design of cost-effective surveillance strategies.